The Impact of Teacher Nonverbal Immediacy on Student Anxiety in English Language Learning: A Correlational Study - Sally, Fauzan Hari Sudding; Fahmuddin, Muhammad (Pascasarjana Universitas Negeri Makassar, 2025)
This study investigates the relationship between teacher nonverbal immediacy and student anxiety in learning English and identifies the specific nonverbal immediacy behavior that most significantly influences student anxiety. A total of 62 students from an English Education Study Program participated in this research. Data were collected using two structured questionnaires measuring lecturer nonverbal immediacy and student anxiety in learning English. Pearson correlation analysis was employed to examine the relationship between the variables. The findings indicate a significant negative correlation between teacher nonverbal immediacy and student anxiety, suggesting that higher levels of teacher nonverbal immediacy are associated with lower student anxiety. Among various nonverbal immediacy behaviors, smiling whether directed at an individual student or the entire class was found to have the most substantial impact in reducing student anxiety. However, one form of nonverbal immediacy, maintaining eye contact with the class while speaking, exhibited a positive correlation with student anxiety. These findings underscore the critical role of teacher nonverbal immediacy in shaping students’ emotional experiences in language learning and highlight the need for educators to adopt effective immediacy behaviors to foster a more supportive learning environment.